2018
DOI: 10.1038/s41433-018-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on the morphologies of the human Schlemm’s canal and trabecular meshwork measured with swept‑source optical coherence tomography

Abstract: PurposeWe aimed to measure the sizes of Schlemm’s canal (SC) and the trabecular meshwork (TM) in healthy individuals and to evaluate variations with age from childhood to old age by using swept-source optical coherence tomography (OCT).MethodsAnterior chamber angle imaging of the superior, inferior, nasal, and temporal regions of the right and left eyes was performed with swept-source OCT. The diameter and area of SC and TM width and thickness were measured manually from OCT images.ResultsA total of 114 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 22 publications
3
41
3
Order By: Relevance
“…Notably, the results of some previously reported studies varied substantially from our results in that they did not show a trend of decrease in TM height with aging 12,17,18 . There may be several reasons for this variation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Notably, the results of some previously reported studies varied substantially from our results in that they did not show a trend of decrease in TM height with aging 12,17,18 . There may be several reasons for this variation.…”
Section: Discussioncontrasting
confidence: 99%
“…Secondly, www.nature.com/scientificreports www.nature.com/scientificreports/ aqueous humour production decreases with increasing age, with less volume flowing into the TM, which may result in reduced TM function, eventually leading to reduced TM size 9 . Thirdly, age-related loss of ciliary muscle movement and change in limbal corneoscleral contour may lead to reduced traction on the TM structure, resulting in decreased TM height [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the largest CSA of SC in PCG eyes was significantly smaller than that of unaffected eyes (3363.91±1082.98 μm 2 compared to 5130.66±1231.90μm 2 , P<0.001). No previous studies have reported the CSA of SC in PCG eyes, but in healthy adults using SD-OCT and SS-OCT, the SC CSA varies rapidly within short distances along its arc, ranging from 4064 ±1308 μm 2 to 13991±1357 μm 2 and may decrease with age [19,[31][32][33]. Eyes with primary open angle glaucoma have a reduced CSA compared with normal healthy controls [33], and reduced SC size may be associated with elevated IOP because the size of SC is related to outflow facility [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…It also provides useful information in planning glaucoma surgery [13,15]. Measurements of the TM and SC in vivo using spectraldomain optical coherence tomography (SD-OCT) or swept-source optical coherence tomography (SS-OCT) have been reported in older children [19][20][21]; however, this modality is not possible in infants and younger children due to the amount of cooperation needed to complete the test, which can only be performed in a seated, awake child. The iUltrasound imaging system is suitable for examination in infants and children under general anesthesia in the supine position and both TM and SC can be clearly identified [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Researchers have used OCT to investigate properties of SC in vivo in mice and humans. 17,[19][20][21][22][23][24][25][26] These studies were limited in axial resolution (2-5 μm) and field of view (0.5-3 mm). Imaging the detailed structure of SC in mice requires overcoming several hurdles.…”
mentioning
confidence: 99%